Methodology for air pollution impact assessment of low emission zones in urban areas of Brazil - the case study of Fortaleza - Dias, Helry Luvillany Fontenele (2018)
The main topic of this research is the development of a methodology for air pollution impact assessment of Low Emission Zones in Brazilian urban areas, using Fortaleza municipality as study city. Low Emission Zones are geographically defined areas where the most polluting vehicles are restricted, in order to reduce the pollutant concentration from mobile sources. For this, methods of air pollution concentrations real data collection in street levels have been adapted and developed. In addition, THOR-AirPAS air pollution modelling system has been adjusted to Fortaleza traffic and meteorological conditions. In this work, the details of experiments for analysis of air pollution real data collection and modelling system using a travel demand model outputs are presented, in this research, TRANUS land use and Transport Model. THOR-AirPAS air pollution assessment system with IFS, OML-Highway meteorological pre-processor, UBM and OSPM have been adjusted and validated, in order to develop the methodology. The experiment carried out in this research showed that, due to delayed technologies in Brazilian vehicle fleet, Low Emission Zones presents significant potential in air pollution reduction in street levels, especially related to NO2, pollutant strongly connected to heavy-duty vehicles (buses and trucks, in majority). The experiment simulated air pollution data showed acceptable errors in comparison with real data collected in analyzed area, however, regional and urban background concentrations real data collection could reduce the observed simulated under and overestimations. Seven different scenarios from state-of-art literature have been proposed to Fortaleza Low Emission Zone, with ULEZ scenario presenting significantly higher potential in air pollution reduction, reaching 9.525 μg/m3 of NO2 reductions (9.22%), 2.201 μg/m3 of global PM10 reductions (9.94%) and 0.630 μg/m3 of Exhaust PM10 reductions (69.25%) for CETESB emission factors, however, feasibility in restriction measures in Fortaleza economic reality suggest the implementation of buses scenario, which brings significant reductions in air pollution, with minor impacts in economic and social aspects of observed region.